Development of a Pt/stainless steel mesh catalyst and its application in catalytic hydrogen combustion. (11th October 2019) - du Preez, S.P.; Jones, D.R.; Bessarabov, D.G.; Falch, A.; Mota das Neves Quaresma, C.; Dunnill, C.W.
Abstract: In this paper, different methods to prepare a Pt/stainless steel mesh catalyst for catalytic hydrogen combustion are reported. Pt was deposited as a thin layer onto stainless steel mesh as a support matrix. Thermal treatment resulted in the formation of uniformly distributed near nano-sized Pt particles on the support's surface. The catalysts were evaluated for catalytic hydrogen combustion, and temperatures of between 420 and 520 °C were achieved and maintained at hydrogen flow rates of 0.2–0.4 Nl/min. SEM and EDX results indicate that stainless steel support calcination promoted the formation of a native oxide layer. This oxide layer stabilized Pt particles during hydrogen combustion procedures, effectively preventing significant Pt aggregation from occurring. It was also found that the Ni content of stainless steel promoted the catalytic hydrogen combustion reaction. Highlights: Pt/stainless steel mesh catalysts were developed and evaluated for catalytic H2 combustion applications. High temperatures associated with catalytic H2 combustion allowed for significant Pt-aggregation. Catalysts with stabilized Pt achieved H2 combustion temperatures of 420–520 °C, which were maintained for several hours. Spontaneous auto ignition occurred on catalysts above 40 °C. Significant reduction in NOx formation occurs from catalytic combustion compared with naked flame combustion.